1985
DOI: 10.1152/ajprenal.1985.249.3.f374
|View full text |Cite
|
Sign up to set email alerts
|

Heteroporous model of glomerular size selectivity: application to normal and nephrotic humans

Abstract: A heteroporous model of the glomerular filtration barrier was developed and used to interpret dextransieving data in healthy volunteers (normal controls), in patients with nephrotic range proteinuria (grouped as grades I-III, according to severity), and in a group of previously nephrotic patients whose proteinuria was in remission ("resolved controls"). Several hypothetical pore-size distributions were compared in terms of their ability to describe the selective increases in the fractional clearance of large d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
177
1
2

Year Published

1987
1987
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(185 citation statements)
references
References 0 publications
5
177
1
2
Order By: Relevance
“…7 The diaphragm's 3D, porous ultrastructure is probably one of the best available morphologic correlates to the barrier's permeability property and sieving function, which enables the filtration of high water flow and small solutes and, at the same time, differential retention of macromolecules within blood. [29][30][31][32] Altogether, the high degree of maturation of the epithelial barrier in the implanted tissue offers unprecedented evidence of the efficiency of organoid-based approaches in terms of functional capacity.…”
Section: Discussionmentioning
confidence: 99%
“…7 The diaphragm's 3D, porous ultrastructure is probably one of the best available morphologic correlates to the barrier's permeability property and sieving function, which enables the filtration of high water flow and small solutes and, at the same time, differential retention of macromolecules within blood. [29][30][31][32] Altogether, the high degree of maturation of the epithelial barrier in the implanted tissue offers unprecedented evidence of the efficiency of organoid-based approaches in terms of functional capacity.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible, however, that the pores we visualized by SEM are located inside the discontinuous and irregular strands described by Wartiovaara et al 15 On the basis of our morphometric analysis, the slit pore size distribution is remarkably in line with the prediction of hypothetical membrane pore sizes derived from experimental measures of glomerular sieving coefficients of neutral test macromolecules of graded sizes and theoretical analysis. 25,26 Of interest, these studies indicated that the most accurate simulation of experimental and clinical data are obtained assuming membrane pores radii to be lognormally distributed. 5,27 The quantitative analysis performed here on the mean radius of the ellipsoidal openings of the filtration slit indicates a log-normal probability distribution in normal and proteinuric conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Together with a proportional rise in the clearance of IgG and IgG4, and an unaltered IgG/IgG4 selectivity index, these observations suggest that a loss of barrier size selectivity is the major cause of proteinuria in our patients. To analyse the size-selective properties of the glomerular barrier, Deen and co-workers [25] have described a theoretical model of solute transport through the glomerular capillary wall. In this model, the major portion of the capillary wall is assumed to be perforated by restrictive pores of identical radius, which differs little between healthy subjects and patients with diabetic glomerular disease, approximating 56 A.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a minor portion of the capillary wall is perforated by large non-discriminatory pores, and behaves in effect as a parallel "shunt pathway" through the filtration barrier. According to the theoretical "isoporous plus shunt" model [25] applied in studies dealing with Type 1 diabetes [4,5,18,23] the radius of the pores in the shunt is so large that they do not discriminate among dextran molecules of up to 60 A. Since the molecular radius of IgG is 55 A, a value equal to that estimated of the restrictive pores of the glomerular membrane, it seems likely that this large protein passes through the glomerular capillary wall via the "shunt pathway" exclusively.…”
Section: Discussionmentioning
confidence: 99%